Social ecology and the right to the city towards ecological and democratic cities - Venturini, Federico; Değirmenci, Emet; Morales, Inés 1976- (Black Rose Books, 2019)
"Cities today are increasingly at the forefront of the environmental and social crisis, and are both a major cause but also a potential solution. Across the world a new wave of urban social movements are arising: movements fighting hostile immigration policies, misogynistic culture, ecological devastation, and social exclusion; movements building economic, social, and political alternatives based on solidarity, equality and participation."--
Keywords: Sozialökologie; Stadt; Sociology, Urban; Urban policy; Urban ecology (Sociology); City and town life; Konferenzschrift -- 2017 -- Thessaloniki